Reversed Phase High Performance Liquid Chromatographic Assay of Isradipine - Prasada Rao, K.V.S.; Neelima, B.; Nagaraju, P.; Prabhakar, G.; Begum, Jameelunnisa (Asian Journal of Chemistry, 2010)
A simple, rapid and precise high performance liquid chromatographic method was developed for the estimation of isradipine in bulk and in pharmaceutical formulations. Isradipine was chromatographed on a reversed phase C18 column using amlodipine as internal standard in a mobile phase consisting of acetonitrile, methanol and water in the ratio of 60 : 30 : 10 v/v. The mobile phase was pumped at a flow rate of 1.0 mL/min, and the eluent was monitored at 290 nm. The calibration curve was linear in the range of 0.5–50 μg/mL. The results were found to be accurate, reproducible and free from interference.